As artes em geral no específico cinematográfico de Sergei Eisenstein - Gozze, Diego Melem [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O propósito desta dissertação é abordar a relação de estreita proximidade entre o cinema e as artes em geral a partir das teorias de Sergei Eisenstein, um dos mais importantes cineastas da primeira metade do século XX e um dos principais teóricos da história do cinema mundial. Para ele, todos os processos e os procedimentos da linguagem cinematográfica já existiam, antes, nas outras formas de arte. Portanto, a partir de sua própria concepção de específico cinematográfico, que compreende justamente a síntese das demais artes, será apresentado, aqui, um panorama geral de sua reflexão sobre o importante lugar delas na linguagem propriamente cinematográfica.

The purpose of this dissertation is to address the close relationship between cinema and all other forms of art in general based on Sergei Eisenstein's theories, one of the most important filmmakers of the first half of the twentieth century, and one of the most important theoreticians in global cinema's history. According to Eisenstein, all the processes and the procedures regarding cinematographic language had already existed before, along other means of art expression. Therefore, from Eisenstein's conception about the cinematographic, specifically regarding to cinema as a subject, which consists precisely in the synthesis of every art form, this document will expose an overview of his thoughts and arguments about their importance and influence in the cinematic language.
The arts in general in the Sergei Eisenstein´s conception about the cinematographic specific
Keywords: Arte; Artes Visuais; Cinema; Audiovisual; Sergei Eisenstein; Art; Visual Arts; Cinema; Audio-visual; Sergei Eisenstein